Analisis Manajemen Risiko Operasional Dengan Pendekatan Metode ERM Pada Kos Kosan Hj Ida - Darmawan, Okki; Pramudia, Davin (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
The purpose of this study is to use Enterprise Risk Management (ERM) techniques to assess operational risk management at Hj. Ida Kos-Kosan. Ida Kos-Kosan. Risks that may disrupt the operation of the boarding house are identified, evaluated, and managed using the ERM process. Direct observation and management interviews were used as data collection methods in this descriptive qualitative research. The findings show that there are five main risks: unauthorized entry of foreigners, damage to boarding facilities, tenants who do not pay rent, product theft, and maintenance delays. Risk scores were calculated as a basis for setting the priority level of handling after each risk was evaluated based on its impact (Severity) and likelihood of occurrence (Occurrence). Late payment of rent has the largest risk score, indicating the need for stricter payment rules and procedures. ERM implementation works well to provide a methodical framework for the process of identifying and managing operational risks. Therefore, ERM can be a useful tool for boarding house managers who want to improve the sustainability and efficiency of the company.